ANALYSIS OF POTENTIAL RENEWABLE ENERGY SOURCES IN THE MUNICIPALITY OF PLJEVLJA IN MONTENEGRO - Vuković, Jelena; Virtič, Peter (Journal of Energy Technology, 2024)
Renewable energy sources include all sources of energy obtained from natural processes, such as wind, solar energy, hydropower, biomass, and geothermal energy. They are the only inexhaustible sources of energy and simultaneously have the least detrimental effect on the environment. This paper reports on an analysis of the potential of renewable energy sources in the municipality of Pljevlja, in Montenegro. The strategic plan is the production and use of clean energy that would have a positive impact on the environment throughout the municipality. In addition, the introduction of new technologies for the exploitation of energy resources opens the potential for new jobs. This method of managing renewable resources would enable the more efficient and healthier use of electricity. This analysis requires the collection of current data, obtained from existing projects, and evaluating and integrating them into a whole. In addition to the analysis of the existing situation of the exploitation of renewable energy sources in Pljevlja, reasons for or against their use are also presented. The project supports environmentally friendly technologies for the production and consumption of electricity generated from natural resources, which is urgently needed in the municipality of Pljevlja, because it is quite polluted due to the negative impact of the existing methods of generating electricity.